This side of hell [large type] - Cogburn, Brett (Cogburn, Brett. Widowmaker Jones western, 2021)
"Card player extraordinaire Poker Alice knows when hold 'em, when to fold 'em, and when to team up with master gunman Newt "Widowmaker" Jones. She's betting on Jones to protect her--and her money--on a treasure hunt in the California desert. Legend has it that a shipwreck is buried in the Salton sands. Some say it's a Spanish galleon that got stuck when the sea ran dry. Other says it's a Chinese junk full of pearls or a Viking ship filled with Aztec treasure. Either way, a lot of very mean and dangerously violent folks would kill to find it. Which is why Poker Annie needs the Widowmaker. In this game, it's winner takes all. Losers die.."--